Hospitalised patients' awareness of their rights: a cross-sectional survey from a tertiary care hospital on the east coast of Peninsular Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; How, Soon Hin; Akter, Seikh Farid Uddin; Shah, Anis (Singapore Medical Association, 2009)
INTRODUCTION: Optimal patient care varies considerably from place to place and is influenced by scientific as well as social developments. The purpose of this study was to investigate awareness and pertinent issues regarding informed consent among hospitalised patients and to determine lapses, in order to improve the standard of care.